Public Health Law and Policy Implications: Justice Kavanaugh. (2019) - Hodge, James G.; Parmet, Wendy E.; Benjamin, Georges; Somers, Sarah; Gulinson, Chelsea
Abstract : Following the confirmation of U.S. Supreme Court Justice Brett Kavanaugh in one of the most sensational jurisprudence events of the modern era, we examine potential repercussions across multiple themes in public health, law, and policy stemming from his ideology and the confirmation process.